Advertising, Habit Formation, and U.S. Tobacco Product Demand. (20th April 2016) - Zheng, Yuqing; Zhen, Chen; Nonnemaker, James; Dench, Daniel
Abstract: The U.S. tobacco market has experienced a shift toward noncigarette tobacco products. We examined the degree of habit formation and the role of advertising for cigarettes, little cigars/cigarillos, large cigars, e‐cigarettes, and smokeless tobacco using market‐level scanner data for convenience stores from 2009 to 2013. Results based on a dynamic demand system show that while all tobacco products are habitual, e‐cigarettes are the most habitual product. More choices of flavors, less restrictions on its use in public places, less documented harmful effects, and a higher upfront cost might explain the higher degree of habit formation for e‐cigarettes. We also find that e‐cigarettes did not substitute for or complement cigarettes. The results imply that e‐cigarettes may serve as a gateway to nicotine addiction but not necessarily to cigarette smoking. Regarding advertising, cigarette magazine advertising did not affect cigarette demand, while e‐cigarette TV advertising increased e‐cigarette demand with a positive spillover to cigarette demand. Such results may help explain e‐cigarettes' recent success in sales and imply that e‐cigarette TV advertising might undermine efforts to reduce cigarette smoking. Advertising was also found to affect the degree of habit formation for cigarettes, large cigars, and e‐cigarettes.